Pengukuran Efektivitas Mesin HLP (Hinge Lid Packer) Dengan Metode Overall Equipment Effectiveness (OEE) Dan Overall Resource Effectiveness (ORE) Di PT. XYZ - Yehezkiel Flobert Silaban; Endang Pudji Widjajati (Pusat Riset dan Inovasi Nasional, 2023)
PT XYZ is a company operating in the cigarette industry. However, with increasing demand for products every year, companies are faced with pressure to fulfill orders in a shorter time and in larger quantities. This often results in intensive use of machines, thereby increasing the risk of occurrencedowntime on the machine. One of the machines that experiences the most damage is the HLP (Hinge Lid Packer), where this can harm the company in various ways. In order to find out how productive and efficient machines are for carrying out production tasks, this study will use the overall equipment effectiveness (OEE) and overall resource effectiveness (ORE) methods to evaluate the HLP machine, which stands for hinge lid packer. Estimated average value of OEE (Overall Equipment Effectiveness) of 75.46% and ORE (Overall Resource Effectiveness) of 65.64%, which is not sufficient for the standard value of 85% set by Japanese Institute of Plant Maintenance (JIPM).